Migrant workers, temporary labour and employment in Southern Europe: a case study on migrants working in the agricultural informal economy of Sicily - Urzi, Domenica (2015)
This thesis explores the migratory experience mainly of Tunisian and Romanian workers in the agricultural informal economy of Sicily (Italy), based on observation and 30 semi-structured interviews. Starting from the reasons behind the decision to migrate and the expectations towards their migratory experience, this thesis argues that family’s needs are central motivational factors for the majority of the people who were part of my study and that the migratory experience tends to transform conventional gendering and parenting roles. The thesis also investigates the strategies used by Tunisian and Romanian migrants to enter the Italian territory and to be recruited in the agricultural sector. My data suggested that social capital (or the lack of it) and social networks are essential resources to enter the Italian territory and its labour market and to remain active within it. Furthermore, the thesis claims that the interaction between the widespread informal employment in Southern Europe and discriminating forms of citizenship creates a paradoxical situation where newly European Romanian workers have more opportunity to negotiate with employers within the informal economy, whereas non-European people must seek contractual work within the formal labour market to justify their immigration status, making them more vulnerable to exploitation by deceitful employers. For this reason an imaginary continuum line has been developed in the last two chapters of the thesis to highlight how discriminatory citizenship status interacts with the informal labour economy of the agricultural sector of Sicily, exacerbating unequal power relations and labour exploitation. By stretching the concept of the ‘camp’ developed by Agamben (1998), the informal economy will be considered as a dimension where people’s rights are severely undermined. The thesis nonetheless asserts that recognition of human dignity and human rights offer a form of utopian critique that might be considered positive as it stands outside the limitations of national forms of citizenship and points to more inclusive ideas of global citizenship.